Identifying emotional components of event-related potentials in the brain functioning of individuals with contamination obsessions and comparison with healthy control group - Seyednezhad Golkhatmi, Seyed Hamid; Dolatshahi, Behrooz; Nosratabadi, Masoud; Shakiba, Shima; Sadjadi, Seyed Alireza (Frontiers in Psychology, 2023)
The present study aimed to examine the emotional components of event-related potentials (ERPs) in individuals with contamination OCD and compare them with a healthy control group. A convenience sample of 45 participants was included, consisting of 30 individuals diagnosed with contamination-type OCD and 15 individuals in a healthy control group. Both groups participated in an ERP study where they encountered a computer-based task presenting both contamination and neutral pictures, while their brain activity was recorded. The data were analyzed using repeated measures analysis of variance (RANOVA) with SPSS-24 and Matlab software. Findings suggest that in P3 amplitude, only individuals with OCD exhibited a larger positive amplitude (p < 0.05) in response to contaminated pictures compared to neutral pictures and in N2 amplitude, only individuals with OCD exhibited a larger negative amplitude (p < 0.05) in response to contaminated pictures compared to neutral pictures in the central vertex (Fz). These findings hold promising implications for the development of more targeted and effective treatments for contamination OCD, emphasizing the importance of emotion-oriented approaches to address the unique neural patterns observed in the frontal vertex.